Enhanced structural and thermal properties of oil palm frond fiber-derived nanocellulose using chemical and mechanical treatments for eco-friendly composites - Randis, Randis; Gapsari, Femiana (Politeknik Negeri Lhokseumawe, 2025)
This study investigates the extraction and characterization of Cellulose Nanofibrils (CNFs) from Oil Palm Frond Fibers (OPFFs) using a combined chemical and mechanical treatment approach. Alkali treatment and bleaching effectively removed non-cellulosic components, increasing the Crystallinity Index (CI) from 58.75% in untreated OPFFs to 73.09% in Chemically Treated Microfibrillated cellulose (CMFs). Subsequent ultrafine grinding further enhanced the CI to 81.93%, demonstrating high purity and improved structural integrity. Thermogravimetric Analysis (TGA) revealed enhanced thermal stability, with the maximum degradation temperature rising from 286°C in OPFFs to 339°C in CNFs. X-ray Diffraction (XRD) analysis confirmed the retention of the cellulose of crystalline structure after all treatments. The novelty of this study lies in the systematic valorization of oil palm frond fibers, an abundant agricultural waste in Indonesia, through an integrated chemical-mechanical process to produce high-performance nanocellulose. These findings demonstrated that OPF-derived CNFs possess superior structural and thermal properties, making them strong candidates for reinforcing eco-friendly polymer composites in sustainable material applications